Relationship of Comorbidity and Age to the Severity of Clinical Symptoms of COVID-19 at Mataram University Hospital - I Made Arya Yogiswara Mahayasa; Moulid Hidayat; Prima Belia Fathana; Indana Eva Ajmala (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
COVID-19 disease is a disease that arises due to infection with the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The purpose of this study was to determine differences in clinical symptoms in elderly and non-elderly patients, as well as patients who had comorbidities and did not have comorbidities. This research is a type of cross-sectional study that was conducted by reviewing the medical records of COVID-19 patients undergoing treatment at Mataram University Hospital in 2021. Data was collected using a consecutive sampling technique. The statistical test used is the Chi-square comparative test. To assess the relationship of age and comorbidities to the severity of symptoms in COVID-19 patients. In this study, 86 subjects were selected based on the inclusion and exclusion criteria applied. The majority of subjects were in the 15-59 year age group, namely 66 (23.3%). With male sex 51 (60.5%) people. The majority of patients with comorbidities experienced severe/critical symptoms 16 (44.4%) and patients without comorbids experienced no symptoms or experienced mild symptoms 35 (35%). The majority of elderly patients experienced severe-critical symptoms 9 (45%) and the majority of non-elderly patients experienced no symptoms or experienced mild symptoms 42 (63.6%). The results of the bivariate analysis test showed a p-value = 0.001 for comorbids with severe symptoms, and a p-value = 0.003 for age with severe symptoms. There is a significant relationship between comorbidities and age on the severity of symptoms in COVID-19 patients.